Psychosocial Predictors of the Sense of Coherence in Adolescents and Young Adults Raised by Single Fathers - Dudak, Anna; Kirenko, Janusz (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
Objective/Aim: The aim of the study was to diagnose the sense of coherence in adolescents and young adults raised by single fathers in the context of their personal resources. Background: Sense of coherence is important in the realisation of developmental tasks, especially in the case of adolescents raised by single fathers because of the specificity of being raised in a single-parent family. Method: The diagnostic survey method was used in the study. The following tools were used: A. Antonovsky’s Orientation to Life Questionnaire (SOC-29) W.H. Fitts’s Tenneessee Self-Concept Scale (TSCS); the Needs and Aspirations Test (Stein’s Self-Portrait); J.S. Norbeck’s Social Support Questionnaire (NSSQ). The research was conducted in Poland. Results: The predictor of the sense of coherence with the greatest extent and strength among the surveyed adolescents raised by single fathers was the self-esteem index related to personal self, which had a negative predictive contribution in all components of the sense of coherence and the global score. The response variable was also significantlyinhibited by the groups of needs for support and entertainment, as well as the ancillary social support index, whereas the self-esteem index related to family self and needs for affiliation were the strongest enhancers. Conclusion: The research confirmed a significant correlation between the sense of coherence and self-esteem, support and needs. It revealed that adolescents raised in a single-father family may develop different attitudes, characteristics and needs than adolescents raised in a two-parent or single-mother family. Implications: Single fathers should do more to encourage their children to undertake coping measures with a view to their future life.